(3GdGaUGM Yf EYQGH CHjGJ eTcdI GdGjVGMs - (3MSf Hf GSO Hf GdMSf GdaGQbj, CHhfUQ GdaGQbj,J (B487 (3g` s
(3ChdgG (B:s
(3CeG HYO aEffi CWGd Gddg HbGc hCOGe YRc hfYeGc hMQS faSc hYdGc deG hbaJ Ydi TQja efRdJc aJejRJ Yf Ggd GdReGf s
(3BNQgG (B:s
(3hcTaJ ef jPH Yfg EP jMJGL ai CcKQeG Edi GdSeGY s
(3HgG GKGQ JeRjb ai BNQ UaMIs
(3HgG fXGe GdJYbjHIs
(3eQJHI Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B538s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs